STRATEGI GURU KELAS DALAM PENGELOLAAN PEMBELAJARAN UNTUK MENINGKATKAN KEAKTIFAN MURID KELAS IV DI SDN 158 PALEMBANG - Karunia, Tria; Handayani, Tutut; Dwi Saputra, Agra; Tri Samiha, Yulia; Paranita, Suzana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Effective learning requires teachers’ ability to manage the learning process in a planned and systematic manner so that students can actively participate in the learning process. This study aims to describe classroom teachers’ strategies in managing learning to improve the activeness of fourth-grade students at SDN 158 Palembang and to identify the supporting and inhibiting factors in its implementation. This study used a qualitative method with a case study approach. The research was conducted at SDN 158 Palembang with the subjects consisting of fourth-grade teachers and students. Informants were selected using purposive sampling. Data were collected through observation, interviews, and documentation using observation guidelines, interview guidelines, and documentation sheets as research instruments. Data validity was tested using source triangulation and method triangulation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that classroom teachers’ strategies in managing learning to improve students’ activeness were carried out through interconnected stages of planning, implementation, and evaluation. In practice, teachers applied an inquiry-based learning strategy that actively involved students through observing, asking questions, participating in discussions, working in groups, and utilizing learning media. Supporting factors included teacher readiness, the use of varied learning media, discussion and group activities, and school support. In contrast, inhibiting factors included differences in students’ learning abilities, varying levels of self-confidence, and limited learning time.